Ultra-stretchable active metasurfaces for high-performance structural color - Ghasemi, Amir; Fang, Rui; Zeze, Dagou A.; Hedayati, Mehdi Keshavarz (AIP advances, 2023)
Metamaterials as artificially structural materials exhibit customized properties unattainable in nature. While dynamic response is highly desired, metamaterials are usually passive and cannot be tuned post-fabrication. A conventional active metamaterial consists of rigid resonators mounted on flexible substrates that permit a limited amount of mechanical tuning. Given that rigid resonators permanently deform or debond under large strains (above 30%), the range of flexibility that is possible with tunable metamaterials is limited. Here, we propose a kirigami-inspired geometry that overcomes this limitation. The proposed design enhances stretchability exceeding 100% when compared with the existing design. A high degree of flexibility is achieved through “stress engineering” at the interface between rigid resonators and flexible substrates. Our design shows that the resonance modes shift at a rate of 3.32 ± 0.1 nm for every 1% change in strain, which is the highest tunability reported thus far. We demonstrate how this new concept can be applied to structural color. Using a single design, we demonstrated the full range of colors for the first time. The novel concept of highly stretchable metamaterials may revolutionize the field and enable its use in applications such as wearable sensors, smart displays, and switchable devices requiring extremely dynamic properties.